Content and comprehensiveness in the nursing documentation for residents in long-term dementia care: a retrospective chart review - Lene Baagøe Laukvik; Merete Lyngstad; Ann Kristin Rotegård; Åshild Slettebø; Mariann Fossum (BMC, 2022)
Abstract Background Insight into and understanding of content and comprehensiveness in nursing documentation is important to secure continuity and high-quality care planning in long-term dementia care. The accuracy of nursing documentation is vital in areas where residents have difficulties in communicating needs and preferences. This study described the content and comprehensiveness of nursing documentation for residents living with dementia in nursing homes. Methods We used a retrospective chart review to describe content and comprehensiveness in the nursing documentation. Person-centered content related to identity, comfort, inclusion, attachment, and occupation was identified, using an extraction tool derived from person-centered care literature. The five-point Comprehensiveness in the Nursing Documentation scale was used to describe the comprehensiveness of the nursing documentation in relation to the nursing process. Results The residents' life stories were identified in 16% of the reviewed records. There were variations in the identified nursing diagnoses related to person-centered information, across all the five categories. There were variations in comprehensiveness within all five categories, and inclusion and occupation had the least comprehensive information. Conclusion Findings from this study highlights challenges in documenting person-centered information in a comprehensive way. To improve nursing documentation of residents living with dementia in nursing homes, nurses need to include residents' perspectives and experiences in their planning and evaluation of care.